PEMBERDAYAAN MASYARAKAT PESISIR DESA BOKORI MELALUI USAHA BUDIDAYA AYAM KAMPUNG SUPER DI KECAMATAN SOROPIA, KABUPATEN KONAWE - Takdir Saili; Gusti Ayu Kade Sutariati; Idrus Salam; Rusli Badaruddin; Syamsuddin Syamsuddin (Vokasi Universitas Halu Oleo, 2023)
Community service activities carried out by a team of Faculty of Animal Husbandry lecturers integrated with the Thematic Community Service Program from the Halu Oleo University Research and Community Service Institute (LPPM) in 2022 will be carried out in Bokori Village, Soropia District, Konawe Regency. Introducing techniques for structuring livestock farmer group organization management to chicken farmers in Bokori Village, Soropia District. This is intended so that farmers can run their livestock business in a more focused and coordinated manner. Introducing environmental management and livestock health so that the surrounding environment is clean and healthy and introduces medical treatment techniques, facsication of livestock. Introducing a system of maintenance, good housing management. Introducing feed to chicken farmers in Bokori Village. The feed technology in question is the technology of making local feed made from fish waste, as a reinforcement for chickens so that livestock needs can be met so that livestock productivity is more optimal. The feed in question is a combination of fish meal, corn and bran. Introducing the system, chicken marketing strategy